Motivating factors for choosing dentistry and plan after graduation - Poudyal, Sijan; Lamichhane, Ram Sudhan; Acharya, Sudeep; Pradhan, Amita (Journal of Chitwan Medical College, 2021)
Background: The knowledge of current motivation to choose dentistry and future plan of dental graduates is critical to health care systems and may result in major change for policies in dental education. This study aimed to assess the motivational factors that influenced students to choose dentistry as a profession and their future plan after graduation. Methods: A cross-sectional study was conducted among the 120 students who have cleared the final Bachelor of Dental Surgery (BDS) examination and were undergoing their mandatory internship program. The data was collected between January 2020 to April 2020. Data analysis was done using Statistical Product and Service Solution (SPSS) version 20 with descriptive and inferential statistics. Results: The leading professional reason was the flexible working hour, 54.8% (n=57). Job stability, 50% (n=52), the desire to help people, 49% (n=51) and a desire to be associated with a health profession, 69.2% (n=72) were the primary reasons on economic, vocational and personal domains respectively. Around half of the participants 52% (n=54) have planned for further study after graduation. Similarly, 28.8% (n=30) of the participants have planned to live and work outside Kathmandu valley, 28.8% (n=30) were planning to live and work within Kathmandu valley. Conclusions: This study found that the flexible working hour, job stability and desire to help people were the motivational factors for choosing dentistry. Majority have planned for further study. In future, only those from outside Kathmandu valley were willing to serve the people beyond the valley.